Hand pump -driven, membrane-based water treatment - Visvanathan, C. (Knovel, 2011)
In 2009, there were 27 million displaced people due to military conflicts alone. Cyclone Nargis in Myanmar (2009), the floods in Pakistan (2010), and the 2011 earthquake and tsunami in Japan highlight the number of devastating disasters occurring around the world in the recent past. Apart from deaths, the number of displaced communities due to these anthropogenic or natural disasters is a huge issue to tackle. Provision for safe drinking water is among the highest priorities during and after any disaster situation.
Keywords: Water -- Purification.; Hand pumps.; Emergency water supply.; elektronické knihy; electronic books